The Botrytis cinerea Xylanase BcXyl1 Modulates Plant Immunity - Yang, Yuankun; Yang, Xiufen; Dong, Yijie; Qiu, Dewen (Frontiers in Microbiology, 2018)
Botrytis cinerea is one of the most notorious pathogenic species that causes serious plant diseases and substantial losses in agriculture throughout the world. We identified BcXyl1 from B. cinerea that exhibited xylanase activity. Expression of the BcXyl1 gene was strongly induced in B. cinerea infecting N. benthamiana and tomato plants, and BcXyl1 deletion strains severely compromised the virulence of B. cinerea. BcXyl1 induced strong cell death in several plants, and cell death activity of BcXyl1 was independent of its xylanase activity. Purified BcXyl1 triggered typically PTI responses and conferred resistance to B. cinerea and TMV in tobacco and tomato plants. A 26-amino acid peptide of BcXyl1 was sufficient for elicitor function. Furthermore, the BcXyl1 death-inducing signal was mediated by the plant LRR receptor-like kinases BAK1 and SOBIR1. Our data suggested that BcXyl1 contributed to B. cinerea virulence and induced plant defense responses.